Dentin hypersensitivity-like tooth pain seen in patients receiving steroid therapy: An exploratory study - Noriaki Shoji; Yu Endo; Masahiro Iikubo; Tomonori Ishii; Hideo Harigae; Jun Aida; Maya Sakamoto; Takashi Sasano (Elsevier, 2016)
To ascertain whether steroid therapy evokes dentin hypersensitivity (DH)-like tooth pain, we performed a study based on compelling evidence from patients receiving steroid therapy. An exploratory study was conducted using a questionnaire for 220 patients prescribed steroids who attended the Department of Hematology and Rheumatology of Tohoku University Hospital. Group comparisons between patients with and without steroid pulse therapy were analysed by statistical means. In this study, any DH-like tooth pain that commenced subsequent to steroid treatment was defined as steroid-derived (SD) tooth pain. The prevalence of SD tooth pain was 17.7% (39/220 patients). SD tooth pain was triggered in many vital teeth by cold and/or hot water (84.2% and 23.7%, respectively) with the pain characterised as continuous, in contrast to typical DH tooth pain. SD tooth pain was significantly more frequent in pulse therapy patients than in non-pulse therapy patients (p < 0.05). Logistic regression analysis adjusted for age and sex showed similar results (odds ratio = 3.74, p = 0.013). Moreover, a positive correlation was observed between the steroid dose and pain score (ρ = 0.642). Dose reduction or discontinuation of steroid therapy relieved SD tooth pain in all cases. Thus, steroid therapy can evoke DH-like tooth pain during treatment.